The lives, loves, and art of Arthur B. Davies - Perlman, Bennard B. (State University of New York Press, 1998)
Drawing on extensive archival research, including previously unavailable letters and diaries, this book covers the breadth and depth of the artist's life and career, from his boyhood in Utica in the 1860s; through his close association with such artists and collectors as Robert Henri, John Sloan, Alfred Stieglitz, Lizzie Bliss, and Abby Aldrich Rockefeller; to his death in Italy in 1928 in the company of his mistress, with whom he had lived a secret double life as "David A. Owen" for more than twenty years. Included are 101 color and black-and-white illustrations of Davies's own work, ranging from romantic dream visions to fragmented cubist forms, as well as photographs depicting his family and friends